PENURUNAN DEBIT PUNCAK HIDROGRAF BANJIR DENGAN PENAMBAHAN LUBANG PORI PADA PAVING BLOCK - Mutiara, Ilhama; Andayono, Totoh (Jurnal Applied Science in Civil Engineering, 2024)
Floods are events that occur as a result of severe hydrological conditions. In general, floods and droughts occur as a result of extreme climatic conditions, hydrological imbalances and inappropriate land use. To reduce the risk of damage due to flooding, flood control efforts are needed. Reducing peak flood discharge is an effort to reduce the impact of flooding by increasing the water that seeps into the ground. This can be done in several ways, such as retention ponds and absorption wells. By increasing the water that seeps into the ground, it is hoped that it can reduce peak flood discharge and minimize the impact of flooding that occurs. One of the pervious paving used is modified paving blocks. This research aims to find out how much runoff occurs and how effective the modified paving blocks are in reducing peak flood discharge.Data collection was carried out experimentally using an artificial rain simulator. The simulator tool that has been designed has dimensions of 120 cm x 60 cm and is equipped with a shower and flowmeter for water discharge. The paving blocks used are hexagons which are commonly used for the surface layer of the soil. The data that has been obtained is analyzed in terms of runoff coefficient (C) and peak flood discharge data using the Nakayasu Synthetic Unit Hydrograph method.Based on the results of the analysis, the runoff coefficient value (C) was obtained, paving blocks without pore holes had the highest runoff coefficient with values ranging from 0.26 – 0.82, paving blocks with a ratio of 2% produced surface runoff coefficient values ranging from 0.25 – 0.81, paving blocks with a ratio of 5%, the resulting surface runoff coefficient value ranges from 0.23 – 0.78, paving blocks with a ratio of 7%, the resulting surface runoff coefficient value ranges from 0.14 – 0.74, and paving blocks with The resulting 10% ratio of surface runoff coefficient values ranges from 0.07 to 0.71. For the Hydrograph method, the results obtained were that the peak flood discharge occurred at the 20th minute, the highest peak flood discharge was found on paving blocks without pores at 11.24m3/sec and the lowest peak discharge was found on paving blocks with a 10% ratio of 8.95m3/sec . So, the reduction in peak flood discharge is 2.29m3/sec or equal to 9.45%.